The bad-tempered ladybird - Carle, Eric. (London : Puffin, 2000)
A grouchy ladybug who is looking for a fight challenges everyone she meets regardless of their size or strength.
K-3.
Keywords: Board books for children; Ladybugs -- Pictorial works -- Juvenile fiction; Temper -- Pictorial works -- Juvenile fiction